Development of Community Potentials in Management of Sustainable Peatlands - Zulkarnaini Zulkarnaini; Abdul Sadad (Iapa Proceedings Conference, 2019)
Tanjung Leban Village, Bukit Batu District, Bengkalis Regency, Riau Province is a village included in the Rokan-Siak Kecil River Peat Hydrology Unit. The existence of this village is very strategic in maintaining the peat swamp ecosystem because its area is included in the Giam Siak Kecil-Bukit Batu Biosphere Reserve area (GSK-BB). But his condition today is quite alarming because it is included in an area prone to repeated land and forest fires. Departing from the above problems, the author wants to raise the focus of the research problem on efforts to develop community potential in peatland management. This study aims to analyze the development of community potential in peatland management in Tanjung Leban Village. This research is a qualitative descriptive study with a sampling technique used is snowball sampling. Research informants are all stakeholders involved and responsible for peatland management. Data collection is done by interviewing, observing, and studying documentation. After the data is collected then it is analyzed using qualitative descriptive analysis. The results showed that the fundamental problem related to environmental management at the study site was the threat of land and forest degradation due to the use of peatland ecosystems that had not been integrated. Therefore it is important to have an empowerment effort with the main goal of improving the quality of life of the community, this is because community empowerment is believed to be able to motivate to change for the better so as to improve the socioeconomic of the family, foster a work culture, and foster a passion for cooperation in development. The programs that are needed by people who live around peatlands are environmental education, the application of environmentally friendly technologies, and the socialization of regulations relating to the protection of ecosystems.